Driver's Personality Traits, Driving Anger, Risky Driving, Aggressive Driving and Road Accident Proneness in Malaysia: A Proposed Safety and Logistic Framework - Muhammad Asyraf Mohd Kassim; Suhaila Abdul Hanan; Ahmad Bashir Aziz (International Journal of Supply Chain Management, 2019)
Road accidents are recognized as the most serious threats that have been haunting worldwide motoring public from children to senior citizens. Human factors such as driver’s personality traits, driving anger and risky driving has been recognized as the contributor to high rate of road accident proneness through their driving style such as aggressive driving. The studies in road accident proneness is still lacking and requires an extensive study, therefore it is important to understand the influence of driver’s personality traits, driving anger and risky driving in predicting road accident proneness through aggressive driving. A conceptual framework is being proposed to investigate the relation and influence of these variables on road accident proneness. The contribution will beneficial for motoring public that want to find solution towards decreasing the rate of road accidents through their personality traits, emotions, attitude and driving style while driving. Besides, the result obtained will give overall benefits to related agencies to understand the impact of human factors and driver’s driving style particularly aggressive driving in reducing road accident.